Gender as determinant in performances in areas of technology and livelihood education - Semin, Johnry Tacio; Cabriga, Florence P.; Polon, Gemma Lyn S.; Alumno, Margaret M. (INVOTEC, 2024)
Technology and Livelihood Education introduce different skills. It is a major called as all in one knowledge that consist of masculine subjects such as Electricity, Carpentry and Agriculture and feminist subjects such as Dressmaking, cooking and Cosmetology and this leads to the differences of males and females in their performances in areas of technology and livelihood education. The researchers studied the level of competence and level of difficulties of males and females in areas of technology. The extent of influence of factors such as experiences, preparation in elementary and culture and beliefs were also identified. The study employed quantitative research design. It was conducted in one public secondary school in La Trinidad, Benguet. The survey questionnaires were administered to sixty students. Based on the statistical findings, the mean scores of males and females showed that they have high level of competence in areas of Technology and Livelihood education. Males and females’ level of difficulty in the competencies in areas of TLE was low. This implies that they can do the activities being assigned to them without close supervision. Meanwhile, on the identified factors that influence the performance of males and females in areas of Technology and Livelihood Education, preparation experiences and preparation in elementary were influential. Finally, the result of T-test proved that there are no differences between gender groups in level of competence, level of difficulty and in extent of the factors that were identified.